The Influence of Tax Incentives on UMKM Taxpayer Compliance. (Study at Kantor Pelayanan Pajak Pratama Subang - Mariana, Syafira; Utami, Anita Dwi; Radia, Dewi Andita Permatasari (LPPM Universitas Sebelas April, 2025)
Based on the phenomenon that occurred at KPP Pratama Subang, many UMKM Taxpayers still do not calculate and report their taxes. This study uses a quantitative method with a survey approach, and the population is taken from the number of UMKM taxpayers registered at KPP Pratama Subang, which amounts to 26,466, so the sample obtained from the Slovin formula calculation is 100 respondents. Data collection was carried out by distributing questionnaires using the simple random sampling method. The data analysis technique used is the Statistical Package For Social Science (SPSS) 25. The results show that the correlation coefficient between Tax Incentives and UMKM Taxpayer Compliance is 15.21%. Based on the research findings, it shows that Tax Incentives have a significant effect on UMKM Taxpayer Compliance